AL-Dibdiba Formation Basin Hydrological Aspects Extraction Using GIS techniques and Quantitative Morphometric Analysis - Hassan, Mustafa; Jawad, Laith (Iraqi Journal of Science, 2023)
The drainage basin’s hydrological aspect studying is considered to be important issue because of their influence (especially in arid to semi-arid regions) on the water management projects, agricultural management projects, and grazing ones. The importance of this study is coming from the fact that AL-Dibdiba formation basin climate is arid to semi-arid and there are human activities (habitation and agricultural) in the east part of it, so the water resources management is needed for this basin. The morphometric analysis illustrates the hydrological aspects in a quantitative form; the problem is the use of the traditional schemes in the calculation processes (such as the topographic map and the planmeter), which coast time and money and accuracy as well (the data generalization case). In this study the morphometric analysis achieved using the SRTM DEM as ancillary data and the ArcGIS 9.3 as a tool for measuring and analyzing.Two new approaches introduced in this study, the first to overcome the No data pixels problem by using the circular focal mean with threshold pixel values, the second approach is basin borders delineation perfectly by applying the 3D analyst tools (interpolate line and create profile graph) on the corrected 30m SRTM.AL-Dibdiba basin drainage pattern derived from DEM showed to be dendritic for the low orders and parallel for the high orders, the morphometric parameters were computed using GIS techniques, then categorized into three classes (linear, areal, and relief) aspects; for the first class there are 938 1st order streams, 428 2nd order stream, 251 3rd order streams,126 4th order streams, and 2 5th ones, the 1st order streams length is 1389520.54m, the 2nd order length is 770265.45m, the 3rd order length is 412819.23m, the 4th order length is 210484m, and the 5th one is 3776m, the 1st order bifurcation ratio is 2.191, the 2nd order bifurcation ratio is 1.705, the 3rd order bifurcation ratio is 1.992, and the 4th order bifurcation ratio is 63. The average (after excluding the anomaly 4th order one value is 1.962, for the second class the drainage density is (1.028kmˉˡ), the drainage frequency is 0.64 stream /km², Drainage Texture is 2.999 stream / km, the elongation ratio is 0.6724, the circularity ratio is 0.34, the form factor is 0.354, the infiltration number is 0.658, and the length of the overland follow is 0.486 km, for the third one the basin relief is 148m, the relief ratio is 0.00169, the channel gradient value is 1.68 m/km, and Constant of Channel Maintenance is 0.97 km.